The Role of Guidance and Counseling Teachers in Providing Classical Services to Increase Student Learning Motivation - Tobiin; Evi Aeni Rufaedah; Akhmad Mujani (Journal Of Psychology, Counseling And Education, 2026)
Learning motivation is a crucial factor in determining students’ academic success, especially in vocational high schools that face unique challenges. This study aims to describe the role of Guidance and Counseling (GC) teachers in classical guidance services to enhance the learning motivation of Grade X TJKT students at SMK Negeri 1 Sindang. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings reveal that GC teachers act as facilitators, motivators, and counselors through creative and interactive services such as group discussions, inspirational videos, and personal reflections. Challenges such as time constraints, limited student openness, and low parental involvement were addressed with emotional approaches and flexible strategies. The study highlights that classical guidance services can foster students’ intrinsic motivation and contribute to a positive learning climate.